Unraveling Brazilian Indian population prostate good health: clinical, anthropometric and genetic features - Mario M. de Lima Junior; Leonardo O. Reis; Ubirajara Ferreira; Ulieme Oliveira Cardoso; Raquel Bueno Barbieri; Gustavo B. de Mendonça; Laura S. Ward (International Brazilian Journal of Urology, 2015)
Purpose To compare dietary, lifestyle, clinical, anthropometric, genetic and prostatic features of Brazilian Indians and non-Indians (Amazon). Methods 315 men, 228 Indians and 89 non-Indians, ≥40 years old were submitted to digital rectal examination, serum prostate specific antigen (PSA), testosterone, TP53 and GSTP1 genotyping, anthropometric, lifestyle, dietary, personal and familial medical history. Prostatic symptoms were evaluated with the International Prostate Symptom Score (IPSS). Results Macuxis and Yanomamis represented 43.6% and 14.5% of Indians respectively who spontaneously referred no prostate symptoms. Mean IPSS was 7, range 3-19, with only 15% of moderate symptoms (score 8-19); Mean age was 54.7 years, waist circumference 86.6 cm, BMI 23.9 kg/m2. Yanomamis presented both lower BMI (21.4 versus 24.8 and 23.3, p=0,001) and prostate volume than Macuxis and “other ethnic groups” (15 versus 20, p=0.001). Testosterone (414 versus 502 and 512, p=0.207) and PSA (0.48 versus 0.6 and 0.41, p=0.349) were similar with progressive PSA increase with aging. Val/Val correlated with lower PSA (p=0.0361). Indians compared to control population presented: - TP53 super representation of Arg/Arg haplotype, 74.5% versus 42.5%, p<0.0001. -GSTP1 Ile/Ile 35.3% versus 60.9%; Ile/Val 45.9% versus 28.7%; Val/Val 18.8% versus 10.3%; p=0.0003. Conclusions Observed specific dietary, lifestyle, anthropometric and genetic profile for TP53 and GSTP1 may contribute to Brazilian Indian population prostate good health.